Analisis Pengaruh Partisipasi Masyarakat Terhadap Pendanaan yang Berdampak pada Daya Tampung dan Pelayanan Madrasah Menurut Persepsi Kepala Madrasah: Studi Kasus pada Madrasah Ibtidaiyah Di Kabupaten Karawang - Nur, Tajudin; Yani, Muh.; Hafidhuddin, Didin (Ta'dibuna: Jurnal Pendidikan Islam, 2016)
Education contributes greatly to the progress of a nation and is a vehicle for translating the messages in the constitution as well as the means to build national character. Terms of regional autonomy that is based on Law No. 32 of 2004, has brought changes in many areas of life, including education. In connection with that, there is the issue of national education policies that need to be reconstructed in the frame work of regional autonomy. This is related to improve the quality of education, improving the efficiency of education management, education and increased relevance Partisipasition public service equalization is indispensable for the implementation of these improvements. This study seeks to provide an overview of community participation in funding and capacity to service pendidikandi Madrasah. This study was conducted to make use of the survey method is a method used to obtain the facts of the existing symptoms and seek factual particulars by using two forms of research is a descriptive study and verification against 134 Elementary School in Khanewal district. From the results, positive influence and signifansi community participation in financing, capacity either partially or jointly to the educational services Elementary School in Karawang district. keyword: Community Participation, Funding, Capacity and Services